2007
DOI: 10.3733/ca.v061n01p31
|View full text |Cite
|
Sign up to set email alerts
|

High spring temperatures decrease peach fruit size

Abstract: O ver the past few decades, models of peach fruit growth and plant development have identified useful principles for assisting growers in making horticultural management decisions. For example, harvest-date prediction models are now available to aid in managing fruit crops (Ben Mimoun and DeJong 1999). The unusually early harvest of California's peach crop in 2004 -which had record high temperatures during bloom time -and attendant difficulties in attaining the fruit sizes desired by the market (DeJong 2005) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 8 publications
1
15
0
1
Order By: Relevance
“…They reported a 2-to 6-d reduction in FDP for every 1°C increase in mean temperature, depending on the cultivar. Lopez et al (2007) found a similar decrease in the number of days from full bloom to reference date in canning and fresh market peaches with an increase in the growing degree hours during the 30-d after full bloom.…”
Section: Resultsmentioning
confidence: 52%
“…They reported a 2-to 6-d reduction in FDP for every 1°C increase in mean temperature, depending on the cultivar. Lopez et al (2007) found a similar decrease in the number of days from full bloom to reference date in canning and fresh market peaches with an increase in the growing degree hours during the 30-d after full bloom.…”
Section: Resultsmentioning
confidence: 52%
“…Thus, delayed (Morin et al 2009) rather than earlier (Myneni et al 1997;Parmesan and Yohe 2003) vegetative bud-break is likely to occur in the south under warming scenarios. Delayed bud-break has been found to hinder flower development in other temperate tree species (Prentice and Helmisaair 1991), which, in turn, can lead to decreased fruit quality (Lopez 2007), fruit set (Rattigan and Hill 1986;Rakngan et al 1996) and fruit ripening (Morin et al 2008). Additionally, delayed bud-break could delay fruit set and seed dispersal.…”
Section: 07°n Latitude)mentioning
confidence: 99%
“…In USA, pricing has favoured large-size fruit (Lopez et al, 2007). Hence, the PDO Calanda norm, which stipulates a minimum peach size is advisable for a better market performance.…”
Section: Discussionmentioning
confidence: 99%